Fabrication of nanofibrous electrospun scaffolds from a heterogeneous library of co- and self-assembling peptides. (15th March 2017) - Maleki, Mahboubeh; Natalello, Antonino; Pugliese, Raffaele; Gelain, Fabrizio
Graphical abstract: Abstract: Self-assembling (SAPs) and co-assembling peptides (CAPs) are driving increasing enthusiasm as synthetic but biologically inspired biomaterials amenable of easy functionalization for regenerative medicine. On the other hand, electrospinning (ES) is a versatile technique useful for tailoring the nanostructures of various biomaterials into scaffolds resembling the extracellular matrices found in organs and tissues. The synergistic merging of these two approaches is a long-awaited advance in nanomedicine that has not been deeply documented so far. In the present work, we describe the successful ES of a library of diverse SAPs and CAPs into biomimetic nanofibrous mats. Our results suggest that suitable ES solutions are characterized by high concentrations of peptides, providing backbone physical chain entanglements, and by random coil/α-helical conformations while β-sheet aggregation may be detrimental to spinnability. The resulting peptide fibers feature interconnected seamless mats with nanofibers average diameters ranging from ∼100 nm to ∼400 nm. Also, peptide chemical nature and ES set up parameters play pivotal roles in determining the conformational transitions and morphological properties of the produced nanofibers. Far from being an exhaustive description of the just-opened novel field of ES-assembled peptides, this seminal work aims at shining a light on a still missing general theory for the production of electrospun peptidic biomaterials bringing together the spatial, biochemical and biomimetic of these two techniques into unique scaffolds for tissue engineering. Statement of Significance: Construction of peptide hydrogels has received considerable attention due to their potential as nanostructures amenable of easy functionalization and capable of creating microenvironments suited for culturing cells and triggering tissue regeneration. They display a superior biocompatibility unmatched by other known synthetic biomaterials so far. However, their applications are confined to body fillers because most of them do spontaneously form hydrogels, while effective tissue regeneration often requires well-defined fibrous scaffolds. In this work, we developed electrospun fibers of various peptides (cross-beta self-assembling, hierarchically assembling, functionalized, co-assembling) and we provided a deep understanding of the crucial phenomena to be taken into account when peptides fibers fabrication. These results open new venues for exploring novel regenerative applications of peptide nanofibrous scaffolds.